Collective action to improve market access for smallholder producers of agroforestry products: Key lessons learned with insights from Cameroon's experience - Gyau, Amos; Franzel, Steven; Chiatoh, Maryben; Nimino, Godwill; Owusu, Kwadwo (Elsevier, 2014)
In recent years, there has been a consensus among development practitioners and academics that improving market access for smallholders will lead to improvement in income and food security. This notwithstanding, market failures often limit smallholders' ability to be linked to markets. To address these challenges, market interventions such as collective action is often proposed as a strategy to reduce the risks of market participation. This review synthesizes the key lessons learned from the use of collective action as institutional arrangement to improve market access for smallholder producers of agroforestry products with insights from an experience in Cameroon. Some key lessons learned for the success of collective action include farmers' own motivation, favorable environment and the inclusion of social activities in the implementation of group activities.